VISUALIZING THE PATH OF A PHOTO TAKER FROM IMAGE METADATA - MAJEED, RASTY (Fırat Üniveristesi, 2021)
Bugünlerde, mobil cihazların adli bilişim çerçevesinde incelenmesi önemli ve aynı zamanda zorlayıcı bir hal almıştır. Mobil cihazlar hem adli bilişim hem de uzmanlar için önemli veriler sunmaktadır. Bir çok uygulama konum verisini kullanarak servislerini verirken, Android cihazlarda ki log dataları konum bilgisi ve diğer hususlarda önemli bilgi barındırmaktadırlar. Konum bilgisi (Enlem-Boylam) kullanılarak, cihazın ve kullanıcının nerelerde bulunduğu öğrenilebilir. Resim meta verisi adli bilişim araştırmalarında önemli bir yer tutmaktadır. Bu meta veri herhangi bir resimin nerede, ne zaman, hangi makine ile çekildiği ve daha fazla bilgiye erişimi sağlar. Her ne kadar literatürde kriminal bilgisini ve bölgesiyle ilgili araştırmalara yardımcı olan uygulamalar mevcut olsa da, bildiğimiz kadarıyla Android cihazlardan çekilmiş fotoğrafların konum bilgilerinden faydalanıp görsel olarak bir harita çizen bir uygulama mevcut değil. Google Photos uygulaması kullanılarak Android cihazları ile çekilen resimlerin gün, saat, konum bilgisi gibi bilgileri güvenlik nedeniyle hafızada saklanmaktadır. Geliştirdiğimiz uygulama, çekilen fotoğraflardan gelen bilgi doğrultusunda kullanıcının güzergahını belirlemektedir. Farklı zaman ve farklı konumlarda çekilen fotoğralar, adli bilişim incelemelerinde kullanılabilirken, geliştirilen bu uygulama Google Harita özelliği ile kullanıcının hareketlerini görselleştirmektedir.

Nowadays, mobile forensics is one of the most challenging aspects of the digital forensic analysis field. Smartphones provide a wealth of interesting data for forensic analysis and investigators. As many applications use location data to enhance or provide their services, the log files of Android devices can contain valuable information and geodata. Based on the geodata (longitude and latitude), it is possible to recreate the whereabouts of the smartphone and its user at specific points and locations in time. Image metadata is an interesting and important part of the information in any digital forensic investigation. It will show and provide information about the exact time and location where the picture was taken, the device that took the picture and much more. Currently, there are many commercial tools available that help investigators of computer forensic analysis to cover and work with a wide range of geographic information that is connected to criminal activities and crime scenes. However, to the best of our knowledge, there are no specific forensic tools available to work with the geolocation of pictures that have been taken by Android devices. Photos captured on Android devices that utilise Google Photos store the date/time and geolocation of the pictures in their properties for security reasons. This developed application depends on these photos to track the user's journey and find all the details of this journey. Photos taken in different places and at different times during a journey can be used in forensic analysis to locate routes between captured photos and show it on Google Maps based on the geolocation details.
Keywords: Mühendislik Bilimleri